Hadronic spectroscopy: Light and heavy mesons - de Castro, A. S.; de Carvalho, H. F.; d'Oliveira, A. B. [UNESP] (Springer Nature, 1985)
We calculate the spectrum of the masses of light and heavy mesons, using a potential that shows confinement and asymptotic freedom for quark-antiquark pairs. From the analysis of the results we estimate the masses of mesons with hottom not yet found experimentally. We discuss the behaviour of the confinement potential under Lorentz transformation and calculate the spin-dependent corrections. We also calculate the electromagnetic decay rates and the leptonic and hadronic decay widths for some mesons. © 1985 Società Italiana di Fisica.
Keywords: 12.85; Composite models of particles